Persepsi Masyarakat Terhadap Mitos dan Fakta Perbankan Syariah - Ashari, Denny Rakhmad Widi; Al Haris, Mohammad Basid; Rifa’i, Akhmad; Hidayati, Atina (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
The diverse perceptions of society regarding Islamic banking, often colored by myths and unexplored viewpoints. The objective of this study is to analyze the public's perceptions of myths and facts surrounding Islamic banking, with a specific focus on Bank Muamalat Branch Tulungagung. The research methodology employed is descriptive qualitative, utilizing in-depth interviews and content analysis. The results reveal that despite prevalent myths, Islamic banking, particularly Bank Muamalat, offers transparent, secure, and cost-competitive services. Furthermore, it is found that Islamic banking is not exclusive to Muslims but accessible to the entire community. These findings contribute positively to understanding the socio-economic dynamics of the community, highlighting the strengths of Islamic banking, and providing a foundation for further research and development in the Islamic banking industry